PERANCANGAN ALAT PERAGA ALFABET SEBAGAI PENGENALAN HURUF KEPADA ANAK-ANAK - SUJARNOTO, Drs. Wisdiarman, M.Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2015)
The creation of learning media aims to add inspiration to teachers and educators in creating instructional media. For children to increase interest and motivation in learning as early as possible. Alphabet learning media design is realized by “Rancang Bangun Method” which is consider the elements of design and condition of child psychology. After going through a long process from determining the object, find ideas, drafting, to a final work. So that to created a draft of learning media with various forms: 1) Standing alfabet, 2) Alfabet kincir-kincir, 3) Standing alfabet angsa, 4) Kotak alfabet, 5) Maze alfabet, 6) Alfabet minion, 7) Alfabet sekolahku dan 8) Alfabet rumahku.Keywords: Design, Learning Media, Children